Dynamism of Sports Diplomacy and Foreign Policy as Correlate of Sports Development in North-Central State, Nigeria - Falaye, Elijah Kayode; Fayomi, Oluwafemi (Universitas Majalengka, 2023)
The central focus of this study was to articulate a better image of Nigeria's sports diplomacy and foreign policy on the development of sports in North – Central state Nigeria. A descriptive research design of survey types was employed for this study. The population for this study comprises all sports administration in the study. A purposive sampling technique was used to select 588 respondents for the study. A researcher-structured questionnaire was used to gather information from the respondents. Three experts validated the instrument and tested for reliability through the test re-test method using Pearson Product Moment Correlation. A correlation coefficient of 0.75